Prevost Virginie, L’aventure ibâḍite dans le sud tunisien. Effervescence d’une région méconnue (viiie-xiiie siècle), Helsinki, Academia Scientiarum Fennica, 2008, 480 p. - Nigst, Lorenz (Revue des mondes musulmans et de la Méditerranée, 2010)
Whoever followed Virginie Prevost’s work over the past years, is well aware of the fact that she established herself as an important scholar on the history of the Ibâḍīs. The volume at hand is entitled « L’aventure ibâḍite dans le sud tunisien. Effervescence d’une région méconnue ». It is an impressive testimony to her ongoing work in that field and a momentous presentation of the results her painstaking research has yielded so far. The volume is impressive both in the wealth of sources it sc...
Keywords: Recension